Scarlet and Black Slavery and Dispossession in Rutgers History - Fuentes, Marisa; Gray White, Deborah (Rutgers University Press, 2016)
The work of the Committee on Enslaved and Disenfranchised Population in Rutgers History. Visit the project's website at http://scarletandblack.rutgers.edu